The influence of character education on the emotional intelligence of informatics and academic students Medicom computer - Bena Ginting; Dinaria Sembiring; Hermelina Ekasari Tarigan (Institute of Computer Science (IOCS), 2023)
This research was conducted to determine the Effect of Character Education on the Emotional Intelligence of Medicom Informatics and Computer Academy Students. This study uses two variables consisting of one dependent variable, namely Emotional Intelligence (Y), while the independent variable is Character Education (X1). The type of research used is explanatory research through associative research, namely research that aims to explain the influence of two or more variables. The sample in this study was 140 people. The data collection method was carried out through questionnaires and literature studies. Data analysis was carried out by testing data quality (validity and reliability), the classic assumption test, the t test (partial test), and the F test (simultaneous test). The results of this study showed that The Effect of Character Education on the Emotional Intelligence of Medicom Informatics and Computer Academy Students is positive, with a correlation coefficient (R) of 0.749 and a determination coefficient (Rsquare) of 0.561. This means that Character Formation (Y) is influenced by 56% of Character Education.